The dietary, productivity, and economic value of swiftlet (Aerodramus fuciphagus) farming in East Kalimantan, Indonesia - Mursidah MURSIDAH; Abubakar M. Lahjie; MASJAYA MASJAYA; YAYA RAYADIN; YOSEP RUSLIM; MEIDI B. JUDINNUR; ANDY ANDY (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mursidah, Lahjie AM, Masjaya, Rayadin Y, Ruslim Y, Judinnur MB, Andy. 2021. The dietary, productivity, and economic value of swiftlet (Aerodramus fuciphagus) farming in East Kalimantan, Indonesia. Biodiversitas 22: 2528-2537. Edible-nest swiftlets have many health benefits. The availability of edible-nest swiftlets from caves is decreasing, while the demand for edible-nest swiftlets is getting higher. Swiftlet farming is carried out to meet this demand. The location of swiftlet farming should be close to the feeding sources. Swiftlet is flying insectivorous animals. A financial feasibility assessment is carried out to determine the feasibility of the business. This study aims to determine the composition of land cover, determine the insect order of feed sources, and analyze the production and financial feasibility of swiftlet farming. The study was carried out from June to December 2019. The composition of land cover was determined using the supervised classification method, the order of insects was known using the insect determination key, while production and financial feasibility were analyzed using the Net B/C, NPV, IRR, and PP methods. The observed location and swiftlet farming were determined purposefully. The results of this study show that the land cover was dominated by shrubs (56.58%) and secondary forest (27.3%); both types of land cover are suitable for swiftlet farming locations. The dominant insects found in shrubs and wetland shrubs are Diptera (78.25%), in rice fields are Diptera (86.7%) and in oil palm plantations are Diptera (29.4%) and Hymenoptera (27.78%). Edible-nest swiftlets harvest begins in the third year, with a production period of between 17-34 years. From the financial feasibility, it can be concluded that swiftlet farming is feasible.